# Equation 4055

Solve the equation and perform the test:

a) 3 (5-2x) + 5x = 5 -3 (x -1)

b) 2 (4y + 3) -3 = 2 - 5 (1 - y)

a) 3 (5-2x) + 5x = 5 -3 (x -1)

b) 2 (4y + 3) -3 = 2 - 5 (1 - y)

### Correct answer:

Tips for related online calculators

Do you have a linear equation or system of equations and looking for its solution? Or do you have a quadratic equation?

#### You need to know the following knowledge to solve this word math problem:

## Related math problems and questions:

- Equation 4293

Solve the equation and perform the test: 2 (4x + 3) - 2 = 6 - 5 (1 - x) - Equation 4300

Solve the equation and perform the test: 1- (x-x/7-1/7) = 7-9x/2 +5/2 - Inequality: 3538

Example1: Solve a linear equation and perform a test: 6x- (3x + 2) = x-8 Example 2: Solve a linear inequality: 3y + 2 * (y + 1) ≥2y-7 - Please

Please determine the solvability conditions of the equation, solve the equation and perform the test: x divided by x squared minus 2x plus1 the whole minus x + 3 divided by x squared minus one is equal to 0: x/(x²-2x+1) - (x+3)/( x²-1) = 0 - Substitution 4644

Solve the system of equations by substitution, comparison, and addition method and perform the test: 4x + y = 5 3x-5y = 21 - Equations 4648

Solve the system of equations by any method and perform the test: 2 (x + y) -3 (y + 2) = -1 x + 2 / 3y-6 = 2 - Calculate 4089

Calculate and perform the test. 3a / 2 + 5/6 = a / 3 - 3/2 - Equation: 36711

Solve the equation: 5x- (6x + 9) = 10x + 2- (x + 5) Please test the left and right sides. Thank you. - Simple equation

Solve the following simple equation: 2. (4x + 3) = 2-5. (1-x) - Equation: 2641

Solve the equation: 3x-2 (x-1) = 1.5x + 0.5 (4-2x) - Equation 25

Solve the following simple equation: 3/4(x+5)=1/2(x+9) - Equation: 4006

Solve the equation: (4x / 2.5x) + (2.4: x) = 3.1. x is a natural number. - Equation: 6200

Solve the equation: 2y = 4 (0.5 + 3/2) -1 - Interesting 8981

Solve an interesting equation: (1 * x) + (2 * x) + (3 * x) + (4 * x) + (5 * x) + (6 * x) = 100 - Function 3345

Perform the inverse function from f: y = 4x + 5. - Equation 7848

Solve the equation with the unknown a: 3 (2a + 1) = (a-3) • 4-5 - Solve 3

Solve a quadratic equation: (6n+1) (4n-1) = 3n²